Disability Lense: Television Framing of Intellectual Disability and Inclusive Education Engagement in Kenya - Lidubwi, Jackline; Bosire, Julius; Mutua, Joan (International Journal of Communication and Public Relation, 2023)
Purpose: The study examined how the framing of intellectual disability in television influenced the level of involvement of learners with intellectual disability in inclusive education in Kenya. Methodology: The study which was guided by the framing theory utilized the descriptive cross-sectional research design. A sample of 10 teachers in inclusive education schools, 10 Sub-County Education Officers, three television stations, three television producers and five key informants from the Kenya Association of the Intellectually Handicapped was drawn. Data was gathered through questionnaires, interview guides and code sheets. Quantitative data was analysed using descriptive and inferential statistics while thematic analysis was used to analyse qualitative data. Findings: The study found that TV programmes aired disability thematic frames that did not support the mainstreaming of intellectual disability in education. The correlation between intellectual disability thematic frames in television and the involvement of learners in inclusive education was not statistically significant. Unique Contribution to Theory, Practice and Policy: The study recommends that representation of disability in media should be more meaningful and TV producers need orientation for the production of disability friendly content for inclusion in TV. Further, there is a need of expanding journalists' capacity to report on pertinent issues that are deemed important by Persons with Disabilities, community in-depth news stories and reports with the objective of raising public awareness about issues important to disability communities. Regarding policy, media regulatory bodies like the Communications Authority of Kenya and the Media Council of Kenya can enforce the existing policies related to disability mainstreaming in the media.